Bad blood - Sandford, John, 1944 Feb. 23- (New York : G.P. Putnam's Sons, 2010)
When a murder suspect commits suicide after his arrest for killing a soybean farmer, Virgil Flowers uncovers a multi- generation, multi-family conspiracy involving a series of monstrous crimes.
Keywords: Flowers, Virgil (Fictitious character) -- Fiction; Government investigators -- Minnesota -- Fiction; Family secrets -- Fiction; Minnesota -- Fiction; Mystery fiction